2020
DOI: 10.1371/journal.pone.0233252
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium marinum phthiocerol dimycocerosates enhance macrophage phagosomal permeabilization and membrane damage

Abstract: Phthiocerol dimycocerosates (PDIMs) are a class of mycobacterial lipids that promote virulence in Mycobacterium tuberculosis and Mycobacterium marinum. It has recently been shown that PDIMs work in concert with the M. tuberculosis Type VII secretion system ESX-1 to permeabilize the phagosomal membranes of infected macrophages. As the zebrafish-M. marinum model of infection has revealed the critical role of PDIM at the host-pathogen interface, we set to determine if PDIMs contributed to phagosomal permeabilizat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 45 publications
4
38
0
Order By: Relevance
“…Second, it is probably that EsxA is not sufficient for mycobacterial phagosome rupture and cytosolic translocation solely, other factors may also contribute to this process. It has been reported that EsxA works with phthiocerol dimycocerosates (PDIM) to mediate phagosome rupture [ 74 , 75 ], and PDIM alone could maintain certain level of hemolysis with Mm [ 76 ]. Also, deletion of other ESX-1 substrates would impact mycobacteria phagosome escape ability [ 17 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, it is probably that EsxA is not sufficient for mycobacterial phagosome rupture and cytosolic translocation solely, other factors may also contribute to this process. It has been reported that EsxA works with phthiocerol dimycocerosates (PDIM) to mediate phagosome rupture [ 74 , 75 ], and PDIM alone could maintain certain level of hemolysis with Mm [ 76 ]. Also, deletion of other ESX-1 substrates would impact mycobacteria phagosome escape ability [ 17 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The combined action of PDIM and ESX-1 in phagosomal membrane disruption was confirmed in Mma [83]. Indeed, a mutant defective in MmpL7, the transporter of PDIM, demonstrated decreased phagosomal permeabilization similarly to the ESX-1 deletion mutant [83] (). Moreover, the MmpL7 mutant retains haemolytic activity, suggesting a different mechanism of membrane damage in red blood cells [83].…”
Section: Introductionmentioning
confidence: 98%
“…Indeed, a mutant defective in MmpL7, the transporter of PDIM, demonstrated decreased phagosomal permeabilization similarly to the ESX-1 deletion mutant [83] (). Moreover, the MmpL7 mutant retains haemolytic activity, suggesting a different mechanism of membrane damage in red blood cells [83]. Mma haemolysis appears to imply another ESX-1 substrate; notably a pe mutant ( MMAR_2894 ) encoding a PE protein secreted by ESX-1, displays a red blood cell lysis defect while maintaining cytolysis activity in macrophages [84].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 Accordingly, phthiocerol dimycocerosates (PDIMs) from M. tuberculosis and M marinum were shown to mask underlying pathogen-associated molecular patterns (PAMPs), allowing evasion from Toll-like receptor (TLR) signaling pathways and contributing to phagosome evasion in conjoint with ESAT-6 secretion systems (ESX) -1. [37][38][39][40][41] Other experimental studies with M. tuberculosis show that PDIM molecules can be transferred to the membranes of macrophages and promote biophysical changes that influence cellular processes such as phagocytosis. 42 Phenolic glycolipids (PGLs) further contribute to the virulence of mycobacteria by hijacking the recruitment of more permissive macrophages to the site of infection via the CCL2-CCR2 (C-C motif chemokine receptor 2) axis, impairing phagolysosome maturation and avoiding triggering the production of proinflammatory mediators by the host immune cells.…”
Section: Introductionmentioning
confidence: 99%